Posted by **Leo** on Saturday, April 6, 2013 at 6:52pm.

2.)If f(x)=3x,g(x)=x-3,and h(x)= the square root of x, find (fogox)(X). I really didn't get this will someone please show me how to do it?

This I what I did to solve for it:

3(x-3)

3(he square root of 25-3

3(5-3)

15-9=6

Ok here is another way I solved for it but I am still not sure if I am doing any of the work right.

f(g(h))(25)

f(g(square root of f(x)))(25)

f(g(1.7))(25)

f(1.7-3)

F(-1.3)

f(25)=3(25)

f(25)=75

Which one is correct and if they are both wrong will you help me get the right answer and understand how to do it?

## Answer this Question

## Related Questions

- math - 2.)If f(x)=3x,g(x)=x-3,and h(x)= the square root of x, find (fogox)(X). ...
- pre calculus - 1.) If h(x)= (fog)(x) and h(x) = 3 over the square root of x+3 , ...
- Math simplifying mixed radicals - Please help me simplify these following mixed ...
- Math simplifying mixed radicals - Please help me simplify these following mixed...
- algebra - could someone please check these roblems for me and if they are not ...
- Math PLEASE HELP ASAP - -PLEASE INCLUDE SOLUTIONS AND EXPLAIN HOW YOU DID IT ...
- Math - Could someone please help me with this math problem? This is what I have ...
- alg.2 - Solve for x... square root x+16=2+square root x+4. I tried doing this ...
- Algebra - Use the quadratic formula to solve the equation. Give exact answers: ...
- Math - (10 Squar root -13)(-5 square root -5) put in standard form a+bi I really...